ChemInform Abstract: Organoselenium and DMAP Co‐Catalysis: Regioselective Synthesis of Medium‐Sized Halolactones and Bromooxepanes from Unactivated Alkenes. Issue 29 (29th June 2016) - Verma, Ajay; Jana, Sadhan; Durga Prasad, Ch.; Yadav, Abhimanyu; Kumar, Sangit
Abstract: A catalytic system for the regioselective cyclization of alkenoic acids towards medium‐sized bromo‐ and iodo lactones is presented.